Nitrogen limitation and calcifuge plant strategies constrain the establishment of native vegetation on magnetite mine tailings - Cross, Adam; Ivanov, D.; Stevens, J.C.; Sadler, R.; Zhong, H.; Lambers, H.; Dixon, Kingsley (2021)
Background and aims: Mine tailings are challenging substrates for ecological restoration, as the establishment of diverse native plant communities can be constrained by a range of edaphic factors. Thus, the ability to restore native vegetation communities will depend upon developing a clear evidence-base as to what types of species and communities are likely sustainably reinstated on such altered substrates. As global tailings production and the cumulative footprint of tailings storage facilities continue to grow, understanding the effect of edaphic filters on community establishment is foundational for developing effective restoration solutions for tailings. Methods: We standardised growth rate estimates derived from nine root and shoot parameters for plants grown in magnetite tailings and natural topsoil, using crops (eight species) to characterise previously identified plant responses and native plants (40 species) to understand the impact of edaphic conditions on the species pool available for restoration. Results: The edaphic conditions of unweathered magnetite tailings select against the majority of native plant species and nutrient-acquisition guilds (approximately 75% of reference floristic biodiversity), with plant development on tailings compared with natural topsoil compromised in a number of variables in all but six species. Plant growth on tailings was limited by a lack of available nitrogen (N) and high alkalinity (pH >9), and seedling growth and development was positively associated with seed N concentration. Calcicole species and species from N2-fixing and cluster root-producing strategies performed better on tailings than calcifuge species and species without specialised nutrient-acquisition strategy or those reliant upon mycorrhizal associations. Conclusions: The return of plant communities native to highly weathered, acidic soils on magnetite tailings is likely unsuccessful, unless strategies to ameliorate substrate hostility through acidification of the soil profile and improving N availability are prioritised.